HISTOPATOLOGICAL OF WHITE RATS' KIDNEY CAUSED BYAPPLICATION OF MIMOSIN FROM SIMPLISIA OF THE LEUCAENA LEAF - Gusti Agung Ayu Alecia Putri Anugrahaeni; I Ketut Berata; Ida Bagus Made Oka; Ni Nyoman Werdi Susari; Ni Luh Eka Setiasih; Luh Made Sudimartini (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Mimosine is a toxic substance contained in Leucaena leucocephala leaves. The toxic effects of mimosine can disrupt several tissues and organs, especially the kidneys. This study aims to determine the histopathology of white rat kidney exposed to mimosine with different doses. Male white rats with Wistar strain, 2 months old and 300-350 g body weight were being used in this study. The 20 rats used were divided into four treatment groups, namely P0 (negative control), P1 (positive control, given standard mimosine 15 mg/head/day), P2 given leucena leaf simplisia at a dose of 50 mg/head/day orally, P3 given leucaena leaf simplisia at a dose of 150 mg/head/day. On the 16th day of necropsy, the skin organs were taken and placed in 10% NBF. After the kidney organs were fixed, histopathology preparations were made using HE staining. Histopathological examination was performed including three lesion variables, namely congestion, bleeding, and inflammation. The severity of the lesions were scored as 0, 1, 2 and 3 respectively for normal, mild, moderate and severe lesions. Data were analyzed using non-parametric Kruskal-Wallis and Mann- Whitney tests. The results of the research showed that the mimosine substance in leucaena leaf simplicia caused some histopathological changes in the kidneys of white rats like congestion, bleeding and inflammation and there was a difference in dose effect for each giving of mimosine from leucaena leaf simplicia, between the dose of 50 mg/head/day and the 150 mg/head/day. Administration of mimosine from leucaena leaf simplicia can cause histopathological changes in the kidneys of white rats and there is an effect of the difference in the dose of mimosine from leucaena leaf simplicia between a dose of 50 mg/head/day and a dose of 150 mg/day. tail/day on changes in kidney pathology of white rats, especially in the form of bleeding and inflammation. With this research, it hoped that in the future further research can be carried out on leucaena leaf simplicia with a longer administration period so that the results obtained are more accurate.